Case Report on Failed Kasai Hepatico Portoenterostomy with Biliary Atresia in 3 years old child - T, Immanuvel.; S, Shanmugachandru.; B, Adhiraj.; Karthickeyan, K.; Sundaram, P. Shanmuga; Dheenadhayalan, M.; Sri, M.K. Sundar (Journal of Neonatal Surgery, 2025)
Biliary atresia is a rare liver disease in children where the bile ducts are blocked or not present in the liver. This case explains a 3 years old child who was previously diagnosed with Biliary Atresia. The Child admitted electively for cholangiogram and asses the possibility of interventional radiology guided Percutaneous transhepatic biliary Drainage insertion for biliary strictures. The child liver enzymes are increased and patient histopathology studies Indicates biliary atresia. The Child was diagnosed with Biliary atresia. Doppler study showed decreased peribiliary echogenicity, short segments of Centre prominent intrahepatic biliary radicals with intervening on dilated duct noted presented intrahepatic strictures. MRCP showed multifocal intrahepatic strictures, cystic dilation central part segment 3 intrahepatic biliary radicals positive. The patient underwent cholangiogram. Medications Used in the Course of Hospitalization are Prograf 1mg and 0.5mg, Mycophenolate Mofetil 250-125mg, Omnacortil 2.5mg and Sirolimus 1mg. Child was hemodynamically stable, vitals are normal, accepting feed well and discharge. Discharge medications are Sirolimus 1mg, Prograf 0.5mg, Ciplox 125mg, Omnacortil 2.5mg, Udcament 2.5ml, Cellcept 250mg.